2019
DOI: 10.1097/tp.0000000000002690
|View full text |Cite
|
Sign up to set email alerts
|

Immune Cell Trafficking to the Liver

Abstract: The human liver is an organ with a diverse array of immunologic functions. Its unique anatomic position that leads to it receiving all the mesenteric venous blood, combined with its unique micro anatomy, allows it to serve as a sentinel for the body’s immune system. Hepatocytes, biliary epithelial cells, Kupffer cells, stellate cells, and liver sinusoidal endothelial cells express key molecules that recruit and activate innate and adaptive immunity. Additionally, a diverse array of lymphoid and myeloid immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 259 publications
0
22
0
Order By: Relevance
“…The liver is enriched with immune cells and cytokines that create a tolerogenic microenvironment [236][237][238][239][240][241][242]. These cells produce anti-inflammatory cytokines (IL-10, TGFβ) or manifest weak or oppositional immune properties that reflect diverse inputs from hepatocytes, sinusoidal endothelial cells, and hepatic stellate cells [238].…”
Section: Overviewmentioning
confidence: 99%
“…The liver is enriched with immune cells and cytokines that create a tolerogenic microenvironment [236][237][238][239][240][241][242]. These cells produce anti-inflammatory cytokines (IL-10, TGFβ) or manifest weak or oppositional immune properties that reflect diverse inputs from hepatocytes, sinusoidal endothelial cells, and hepatic stellate cells [238].…”
Section: Overviewmentioning
confidence: 99%
“…The expression of cell death-related genes was not altered in GILZ KO mice, thus we concluded that the enhanced susceptibility to CCl 4 -induced LF depends on other cellular processes. LF development is strictly associated with inflammation 4 , 70 72 . We found that GILZ controls the leukocyte recruitment to the liver during initial and chronic phases of LF development, following CCl 4 -induced liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…The liver receives blood from both the portal vein and the hepatic artery. In the portal vein, the liver confronts various antigens from digested food and the gut microbiome under physiological conditions (13). The immune reaction is tightly controlled and regulated, generating liver-protective immunity while these antigens pass through sinusoids.…”
Section: Introductionmentioning
confidence: 99%